Powtoon Learning Media Contextually Based on Thermochemistry Materials to Increase Students' Learning Motivation - Azizah, Nur; Kamaludin, Agus (Universitas Islam Negeri Raden Intan Lampung, 2023)
Thermokinetics material is a conceptual and abstract topic in chemistry. Therefore, instructional media is needed to make thermokinetics more tangible to enhance student motivation in learning chemistry. The objective of this research is to develop a contextual-based instructional medium using Powtoon for thermokinetics and determine the quality of the developed product. The research method employed is Research and Development, adapting the 4-D model (Definition, Design, Development, and Dissemination). Research instruments include a product quality assessment sheet and a student response sheet. Based on evaluations by subject matter experts, media experts, and chemistry educators/reviewers, the percentages obtained are 93%, 95%, and 90%, respectively, belonging to the